Archaeological Surveys In The Valley Of The River Tskhenisthkali (Lentekhi Municipality) - Kvitsiani, Zviad; Jibladze, Leri; Oqropiridze, Aleksandre (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2017)
Institute of the Archeology under Ivane Javakhishvili Tbilisi State University(TSU), conducted archeological expeditions in Svaneti (Head of the expedition - Prof. Z. Kvitsiani) from 2011 to 2016. According to the order of archeological commission of the national agency of the preservation of cultural heritage of Georgia, students of TSU participated in archaeological excavations held in the highlands of Enguri, Nenskra, Dolar, Nakris and Tskhenistskali river valleys in April 2017. From October 4 to October 20, 2017 archeological works were carried out in the Lentekhi municipality (head of the expedition - prof. Z. Kvitsiani) organized by Tbilisi State University. The aim of the archaeological survey was to identify archeological objects, conduct surface inspection, observe their structures, perform small cleaning works on them. At the same time, we were collecting information about the archaeological artefacts which are scattered around among the local people. 1. The first object was discovered in a village Babil, at place called “Lenskra”. A simple type of chapel and church, these types of complexes generally belongs to the early medieval period. 2. Archaeological surveys were conducted on both coastal areas of riv. Tskhenistskali, in the north-east direction, in the Choluri and Lashkhevi communities. Particularly, in Levesheri (“Lost Land “), we did not find an archaeological object, but in a village Jakhunderi we discovered a bronze spear, III mill. BC, also we found bronze Colchian axe in a village Sasashi, they are now stored in Tsageri museum. 3. Also, archeological activities were carried out in the village Khofuri, our team visited the church located in George Kurasbedian’s homeland. 4. The members of Svaneti archeological expedition visited and reevaluated the circumstances of the “Babil Bronze Collection” discovery in 2001. We found out that it wasn’t burial inventory, but a treasure. 5. Archeological survey was carried out on the left bank of riv. Tskhenistskali, village Nanari where Bronze Age Colchian axe was discovered. Thus, in the framework of the archaeological expeditions in the Lentekhi municipality area, we worked in four notable archaeological sites: Nanari, Khopuri, Kvedreshi and Babili. It is necessary and urgent to study the above mentioned archaeological objects.